2023
DOI: 10.3390/jcm12020479
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Foraminal Parameters with Patient-Reported Outcomes in Patient with Degenerative Lumbar Foraminal Stenosis

Abstract: The relationship between quantitative anatomic parameters in MRI and patient-reported outcomes (PROs) before and after surgery in degenerative lumbar foraminal stenosis remains unknown. We included 58 patients who underwent transforaminal lumbar interbody fusion (TLIF) for single-level degenerative disc disease with foraminal stenosis between February 2013 and June 2020. PROs were evaluated using the visual analog scale (VAS) for back and leg pain, Oswestry Disability Index (ODI), and EuroQol-5D (EQ-5D). The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…They tried to determine whether gender could be a factor differentiating these dimensions. The topic of intervertebral foramen was also reported by Giles [19], Fujiwara [20], and Lin [7]. The last of the studies cited showed that the anatomical parameters of the intervertebral foramen, assessed by preoperative MRI, were independently correlated with the results reported by patients with degenerative lumbar foramen stenosis.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…They tried to determine whether gender could be a factor differentiating these dimensions. The topic of intervertebral foramen was also reported by Giles [19], Fujiwara [20], and Lin [7]. The last of the studies cited showed that the anatomical parameters of the intervertebral foramen, assessed by preoperative MRI, were independently correlated with the results reported by patients with degenerative lumbar foramen stenosis.…”
Section: Discussionmentioning
confidence: 61%
“…Therefore, it is necessary to improve the diagnostic procedures related to the described disease entity [6]. It is estimated that stenosis of the intervertebral foramina is a problem for about 8-11% of the population [7]. Pathologies occurring within the intervertebral disc may lead to changes in the parameters of the intervertebral foramina.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation